Citrus bergamia: Kinetics of Antimicrobial Activity on Clinical Isolates - Angela Quirino; Valeria Giorgi; Ernesto Palma; Nadia Marascio; Paola Morelli; Angelo Maletta; Francesca Divenuto; Giuseppe De Angelis; Valentina Tancrè; Saverio Nucera; Micaela Gliozzi; Vincenzo Musolino; et al. (MDPI AG, 2022)
Background: The inappropriate use of antibiotics has increased selective pressure and the spread of multi-drug-resistant (MDR) pathogens, which reduces the possibility of effective treatment. A potential alternative therapeutic approach may be represented by essential oils, such as the distilled extract of bergamot (Citrus bergamia Risso et Poiteau). Such natural products exercise numerous biological activities, including antimicrobial effects. Methods: This work aimed to evaluate the kinetics of the bactericidal and fungicidal activity of the distilled extract of bergamot on MDR bacteria and fungi from clinical specimens using the time-kill assay. Furthermore, the antimicrobial activity of the distilled extract of bergamot on the morphology and cellular organization of clinical pathogens was evaluated by confocal laser scanning microscopy. Results: Our results demonstrated that the distilled extract of bergamot exhibited significant antimicrobial activity and a specific bactericidal effect against the bacterial and fungal strains tested. Furthermore, confocal microscope images clearly showed compromised membrane integrity, damage and cell death in bacterial samples treated with the distilled extract of bergamot. In addition, progressive alterations in cell-wall composition, cytoplasmic material and nucleus structure triggered by exposure to the distilled extract of bergamot were identified in the fungal samples considered. Conclusions: Our data suggest that the use of essential oils, such as distilled extract of bergamot (Citrus bergamia Risso et Poiteau), can represent a valid alternative therapeutic strategy to counteract antibiotic resistance of pathogens.